2015
DOI: 10.1016/j.socscimed.2015.03.038
|View full text |Cite
|
Sign up to set email alerts
|

A blessing I can't afford: Factors underlying the paradox of happiness about unintended pregnancy

Abstract: An unresolved paradox in the measurement and interpretation of unintended pregnancy is that women frequently report feeling happy about pregnancies they also classify as unintended (i.e. they have incongruent intentions and feelings). This study explores the underlying reasons why women profess such happiness and how these relate to their motivations to avoid pregnancy. Between September 2013 and February 2014, semi-structured in-depth interviews were conducted with 27 women (8 white, 19 Latina) selected from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
110
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 113 publications
(120 citation statements)
references
References 33 publications
(34 reference statements)
6
110
0
Order By: Relevance
“…Recent authors have called for new constructs that more fully capture the multidimensional nature of pregnancy intention (10, 12, 18, 38), especially as unintended pregnancies that are met with happiness may very well differ in terms of maternal and child health outcomes (9, 21, 50, 5762). The London Measure of Unplanned Pregnancy is one such measure that has been validated in multiple populations (42, 6367) that may offer promise for future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Recent authors have called for new constructs that more fully capture the multidimensional nature of pregnancy intention (10, 12, 18, 38), especially as unintended pregnancies that are met with happiness may very well differ in terms of maternal and child health outcomes (9, 21, 50, 5762). The London Measure of Unplanned Pregnancy is one such measure that has been validated in multiple populations (42, 6367) that may offer promise for future studies.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a qualitative study of women in Texas found that even as they often used inconsistent or ineffective contraceptive practices, low-income respondents expressed financial concerns about the cost of having another child (Aiken et al 2015). Further, recent work based on interviews with low-SES men found substantial ambivalence about having a child and some evidence that economic resources play at least some role in their discussions of nonmarital fertility (Augustine et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…29 Findings indicated that women made a clear distinction between the questions on intentions and those on feelings, and understood that the former asked about the timing of their anticipated childbearing and the latter asked about their emotional response to a hypothetical future pregnancy.…”
Section: Methodsmentioning
confidence: 99%